Detox Fashion Supply Chain - Muthu, Subramanian Senthilkannan (Textile Science and Clothing Technology, 2017)
This first volume on detox fashion discusses various interesting topics including a Toxic-Free Supply Chain for Textiles and Clothing; Environmental Issues in Textiles; Global Regulations, Restrictions & Research; Making the Change: Consumer Adoption of Sustainable Fashion; and Strategies for Detoxing Your Wardrobe. It provides an overview of the chemical-related issues confronting the fashion sector, summarizes global regulations, and discusses how to make the change by changing consumers' attitude towards adopting sustainable fashion, as well as the best strategies for detoxing our wardrobes.